A new Mexican species of Belonuchus Nordmann (Coleoptera, Staphylinidae) - Rodríguez, William David; Navarrete-Heredia, José Luis (Zootaxa, 2016)
A new species of Belonuchus Nordmann, 1837 is described based on 118 specimens from Cerro de Garcia, Jalisco, Mexico. Belonuchus cifuentesi Rodríguez & Navarrete-Heredia sp. nov. was primarily collected associated with Agave inaequidens, and is similar to B. arizonicus Casey, 1915 but differs mainly in the structure of the aedeagus and color pattern.